PENGEMBANGAN KOMODITAS HORTIKULTURA UNGGULAN LEMBANG TADONGKON BERDASARKAN ANALISIS LQ, SHIFT SHARE, DAN TIPOLOGI KLASSEN - Siradjuddin, Irsyadi; Anshar, Muhammad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Lembang Tadongkon is a highland area with considerable potential for horticultural development. Its fertile soils, deeply rooted farming traditions, and the availability of local labor make it highly suitable for development as an agropolitan hub. This study aims to identify leading horticultural commodities in the region and formulate strategies for their sustainable development. The methods employed include Location Quotient (LQ) analysis, Shift Share analysis, and SWOT analysis. Data were obtained from both primary and secondary surveys and analyzed in two stages: qualitative SWOT (SWOT matrix) and quantitative SWOT (weighting and scoring). The results of the LQ, Shift Share, and Klassen typology analyses for eleven horticultural commodities in Lembang Tadongkon reveal that five commodities have LQ >1 spinach (1.21), cabe katokkon chili (1.07), long beans (1.24), water spinach (1.09), and eggplant (1.38) indicating that they are base commodities with strong development potential. However, only tomatoes exhibited positive growth in the Shift Share analysis (0.84), while the remaining commodities showed negative growth. According to the Klassen typology, all commodities remain in the “Lagging” category, as both their contribution and growth rates are below the regional average. Accordingly, strategies are required to enhance cultivation technology, post-harvest management, and institutional capacity to transform base commodities into sustainable leading commodities. Quantitative SWOT analysis positions Lembang Tadongkon in Quadrant I (progressive), indicating that the area possesses substantial strengths and opportunities for integrated development. Recommended strategies include production expansion, downstream product development, strengthening farmer organizations, and leveraging agro-tourism potential based on local flagship commodities.